One-off low-dose CT for lung cancer screening in China: a multicentre, population-based, prospective cohort study. Issue 4 (April 2022) - Li, Ni; Tan, Fengwei; Chen, Wanqing; Dai, Min; Wang, Fei; Shen, Sipeng; Tang, Wei; Li, Jiang; Yu, Yiwen; Cao, Wei; Xu, Yongjie; Qin, Chao; et al.
Summary: Background: Lung cancer is the leading cause of cancer death worldwide. Data on the effectiveness of one-off low-dose CT (LDCT) in reducing lung cancer mortality and all-cause mortality are needed to inform screening programmes in countries with limited medical resources. We aimed to evaluate the effectiveness of one-off LDCT screening in the early detection of lung cancer in China. Methods: A multicentre, population-based, prospective cohort study was done in 12 cities of eight provinces across China, recruiting individuals aged 40–74 years who were asymptomatic for lung cancer with no lung cancer history. Participants were classified as at high risk or low risk of lung cancer using a sex-specific risk score that incorporated cigarette smoking, level of physical activity, occupational exposures, history of chronic respiratory diseases, family history of lung cancer, diet, and passive smoking (women only). Participants at high risk were invited for a one-off LDCT scan and were classified into screened and non-screened groups on the basis of whether or not they had the scan. Lung cancer incidence density, lung cancer mortality, and all-cause mortality were calculated for the screened and non-screened groups. The effectiveness of a one-off LDCT scan was evaluated by a comparison of the screened and non-screened groups in terms of lung cancer mortality and all-cause mortality in the period from cohort entry until administrative censoring (June 20, 2020). Inverse probability weighting was adopted to account for potential imbalanced factors between the two groups and Cox proportional hazards model was used to estimate the weighted associations between mortality and one-off LDCT scans. Findings: Between Feb 19, 2013, and Oct 31, 2018, 1 032 639 individuals were assessed for eligibility. 1 016 740 participants were enrolled in the study, of whom 3581 had a lung cancer diagnosis after a median follow-up of 3·6 years (IQR 2·8–5·1). Among the 223 302 participants at high risk, 79 581 (35·6%) had an LDCT scan (screened group) and 143 721 (64·4%) did not (non-screened group). After inverse probability weighting, lung cancer incidence density was 47·0% higher (hazard ratio 1·47 [95% CI 1·27–1·70]; p<0·0001), lung cancer mortality was 31·0% lower (0·69 [95% CI 0·53–0·92]; p=0·010) and all-cause mortality was 32·0% lower (0·68 [0·57–0·82]; p<0·0001) for participants in the screened group compared with those in the non-screened group. Interpretation: One-off LDCT screening was associated with significantly lower lung cancer mortality and all-cause mortality in a large population in China. Our results point to the promise of one-off LDCT screening in countries with limited medical resources. Further studies are needed to explore interactions by subgroup—including sex, age, smoking status, and economic status—to develop population-specific screening strategies. Funding: Ministry of Finance and National Health Commission of the People's Republic of China. Translation: For the Chinese translation of the abstract see Supplementary Materials section.